Author Response: Prevalence and Significance of Impaired Microvascular Tissue Reperfusion Despite Macrovascular Angiographic Reperfusion (No-Reflow). (24th January 2023) - Ng, Felix C.
Abstract : We thank the readers for their interest in our research. 1 Methodological differences may account for the discrepancy in the reported rates of no-reflow. Using prospective trial data with prespecified follow-up perfusion imaging, we assessed 146 of 147 (99%, 1 patient was excluded because of hemicraniectomy) patients with TICI 2c/3 angiographic reperfusion, 1 while only 25% (n = 51/203) were assessed in the study by Ter Schiphorst et al. 2 This is important because the association between no-reflow and poor neurologic recovery (24-hour NIHSS 7 [no-reflow] vs 2 [without no-reflow]; p < 0.0001) may confer inherent selection bias in observational studies because patients with more severe symptoms, such as those with no-reflow, may be less likely to complete prolonged research MRIs and therefore be excluded from analysis. Despite intermodality differences, a recent study by Rosso et al. found a similar rate of hypoperfusion on arterial spin labeling among patients with complete recanalization (n = 34/140; 24.3%), 3 compared with our analysis (25.3%) using perfusion-weighted imaging and CT perfusion. 1 Rosso et al. added to the growing body of literature that demonstrates a remarkably consistent prevalence of no-reflow across imaging modalities (transcranial Doppler 27.9%, 4 single-photon emission computed tomography 25% 5 ), which is in support of the external validity of our results.